รูปแบบเครือข่ายมหาวิทยาลัยในการบรรลุผลประโยชน์ร่วมกัน ของการพัฒนาภูมิภาคสู่ประชาคมอาเซียน / A Model of University Networks to Achieve the Mutual Benefits of Regional Development toward ASEAN Community - ศรเนตร อารีโสภณพิเชฐ และพันธ์ศักดิ์ พลสารัมย์ / Vorachai Viphoouparakhot, Sornnate Areesop, วรชัย วิภูอุปรโคตร (Journal of Community Development Research (Humanities and Social Sciences), 2017)
การวิจัยนี้มีวัตถุประสงค์ในการศึกษา คือ การศึกษาสภาพปัจจุบันของเครือข่ายมหาวิทยาลัยในระดับภูมิภาคอาเซียน แนวปฏิบัติที่ดีของเครือข่ายมหาวิทยาลัยและการพัฒนารูปแบบเครือข่ายมหาวิทยาลัยที่เหมาะสมกับภูมิภาคอาเซียนในปัจจุบัน เพื่อการบรรลุผลประโยชน์ร่วมของการพัฒนาภูมิภาคสู่ประชาคมอาเซียน เป็นการวิเคราะห์เอกสารทางวิชาการ และการสัมภาษณ์จากกลุ่มตัวย่าง จากการวิเคราะห์สภาพปัจจุบันและแนวปฏิบัติที่ดีของเครือข่ายมหาวิทยาลัยในประเทศไทยและภูมิภาคอาเซียน ทำให้ได้องค์ประกอบที่สำคัญของเครือข่ายมหาวิทยาลัย 6 ด้าน (The POWERS: Elements of Regional University Network) คือ ด้านพันธมิตรและสมาชิกเครือข่าย ด้านวัตถุประสงค์และพันธกิจ ด้านคณะทำงาน ด้านการทำงานร่วมและบรรลุผลประโยชน์ร่วมกัน ด้านการจัดการในระดับภูมิภาค และด้านผู้มีส่วนได้ส่วนเสียอื่นๆ และนำองค์ประกอบที่ได้มาสู่ขั้นตอนการพัฒนารูปแบบเครือข่ายมหาวิทยาลัยในระดับภูมิภาคอาเซียนที่มีความเหมาะสมในบริบทปัจจุบัน เพื่อเป้าหมายการบรรลุผลประโยชน์ของการพัฒนาภูมิภาคและมุ่งมั่นสู่การเป็นประชาคมอาเซียนโดยสมบูรณ์ ผลการศึกษาผู้วิจัยได้รูปแบบของเครือข่ายมหาวิทยาลัยในระดับภูมิภาคอาเซียน คือ รูปแบบการบริหารจัดการเครือข่ายมหาวิทยาลัยในระดับภูมิภาคสร้างพลังความร่วมมือในทุกภาคส่วนของภูมิภาคอาเซียน (The POWERS-M : Model for the Regional University Network Management) เป็นการใช้ทรัพยากรร่วมกันของมหาวิทยาลัยกับผู้มีส่วนได้ส่วนเสียเพื่อการทำงานร่วมกันในการพัฒนาภูมิภาคอาเซียน แบ่งเป็น 4 แนวทาง คือ การเสริมสร้างการวิจัยและนวัตกรรมเพื่ออาเซียน การส่งเสริมผู้ประกอบการและการพัฒนาภาคธุรกิจ สนับสนุนการพัฒนาทุนมนุษย์และการเพิ่มทักษะแรงงานเพื่อภูมิภาค และการยกระดับการพัฒนาสังคมและวัฒนธรรมเพื่อความเป็นอัตลักษณ์ของภูมิภาค รูปแบบนี้จะทำให้มหาวิทยาลัยในอาเซียนเกิดพลวัตพลังการขับเคลื่อนร่วมกัน (Dynamic of Driven Together) มีปัจจัยแห่งความสำเร็จที่สำคัญ 4 ด้าน คือ การมีแรงจูงใจและเป้าหมาย ความไว้วางใจและมุ่งมั่น ระดับความสัมพันธ์ของเครือข่าย ทรัพยากรและการบริหารจัดการ      The purposes of this research were to study ASEAN University Network (2015) in present with the best practice of university networks and to develop a model of university networks to achieve the mutual benefits of regional development toward ASEAN Community. This research was conducted by analyzing from academic documents and interviewing specific samples. There were 2 processes of analyzing that are 1) Analysis current situation and best practices of university networking in Thailand and within ASEAN in order to get the elements of university networks, and 2) Using the elements in the first process to develop a model of university networks to achieve the mutual benefits of regional development toward ASEAN Community which practicability with current situation. The research revealed that the significant elements of ASEAN Community University Network comprised of 6 elements that called The POWERS including P artnership and Membership, O bjectives and Missions, W orking Group, E ngagement and Mutual Benefit, R egional Management, and S takeholder. These elements are then translated into the development of a model for ASEAN-level university network in a manner that suits the current context. This is for the benefit of regional development leading to the full ASEAN integration. The models for ASEAN-level university network or so-called ‘Model for the Regional University Network Management (The POWERS-M) are the research results achieved by the author. They involve resource sharing between universities and stakeholders for the purpose of the collaboration for ASEAN development and have 4 parts: strengthening research and innovation for ASEAN, supporting traders and developing of business section, encouraging human capital development and increasing workers skill for regional, and enhancing social and traditional development for regional identities. The 4 guidelines to push university in ASEAN toward to Dynamic of Driven together with the essential success factors are Motive and Goal, Trust and Commitment, Relationship network and Resource Management.
Keywords: องค์ประกอบเครือข่ายมหาวิทยาลัย การบริหารจัดการเครือข่ายมหาวิทยาลัยในภูมิภาค พลวัตพลังการขับเคลื่อนร่วมกัน; Elements of University Network, Regional University Network Management, Dynamic of Driven Together